Outline of Proteins and Signaling Pathways Involved in Heart Failure - Bi, Qun (Current Protein and Peptide Science, 2012)
Heart failure (HF) is a condition with high mortality worldwide characterized by persistent progression. Myocardial hypertrophy is a dominant feature during the early stage of HF. The development of HF is a complex process related to a series of physiologic and molecular factors. Although the treatment of HF has been changed during the past century, the knowledge on its molecular mechanism is still very limited. The review herein tries to touch the molecular basis underlying HF and discusses the relevance between HF and other diseases such as thrombosis. Furthermore, we believe that the global alterations during progression of HF revealed by high content screening techniques may facilitate our understanding on HF, and thereby the development of new therapeutics with less side effect.
Keywords: Extracellular matrix